Supporting Technical Debt Cataloging with TD-Tracker Tool. (17th September 2015) - Foganholi, Lucas Borante; Eduardo Garcia, Rogério; Medeiros Eler, Danilo; Celso Messias Correia, Ronaldo; Olivete Junior, Celso
Abstract : Technical debt (TD) is an emergent area that has stimulated academic concern. Managers must have information about debt in order to balance time-to-market advantages and issues of TD. In addition, managers must have information about TD to plan payments. Development tasks such as designing, coding, and testing generate different sorts of TD, each one with specific information. Moreover, literature review pointed out a gap in identifying and accurately cataloging technical debt. It is possible to find tools that can identify technical debt, but there is not a described solution that supports cataloging all types of debt. This paper presents an approach to create an integrated catalog of technical debts from different software development tasks. The approach allows tabulating and managing TD properties in order to support managers in the decision process. It also allows managers to track TD. The approach is implemented by TD-Tracker tool, which can integrate different TD identification tools and import identified debts. We present integrations between TD-Tracker and two external tools, used to identify potential technical debts. As part of the approach, we describe how to map the relationship between TD-Tracker and the external tools. We also show how to manage external information within TD-Tracker.